Media, the Cesarean Fetish, and the Objectification of Birth - Barros, Luciana de Amorim; Ericson, Sóstenes (Entrepalavras, 2025)
This article analyzes the discursive functioning in constructing meanings about childbirth, focusing on the valorization of caesarean sections and the objectification of birth. Grounded in Based on materialist Discourse Analysis and articulated with concept of commodity fetishism (Marx, 2013), the study investigates how the media operateoperates in the naturalization of hospital practices, the aestheticization of childbirth, and the transformation of the female body into a commodity. Based drawing on news report of Veja São Paulo, the analysis it demonstrates how the formation of an imaginary is constructed that linksassociates caesarean delivery towith progress, comfort, and social status, while displacingsimultaneously detaching birth from its symbolic and relational dimensions. The analysis explores how these practices are shaped by biomedical capitalism and market dynamicslogic, obscuring alternative and humanized waysforms of giving birth. The study concludes that childbirth, as both a physiological and political experience, is increasinglyhas been progressively captured by discourses of consumption and spectacle, although challenged though still contested by resistances that seek to reframe its meanings.